Media & values : intimate transgressions in a changing moral and cultural landscape - Morrison, David E. (Intellect, 2007)
Media & values investigates the moral performance of the media. Based on an exhaustive number of focus groups, surveys, and interviews with senior media staffers in the United Kingdom and Europe, this book charts the changing status of the media as a moral voice. The authors argue that television has lost the authority to espouse a single vision of the proper way to live, and instead reflects the norms of a variety of social groups. This groundbreaking volume addresses the lack of moral certainty reflected both in television programs and their audiences.